A Bibliometric Analysis and Visualization of Current Research Trends in the Treatment of Cervical Spondylotic Myelopathy. Issue 6 (July 2021) - Yin, Mengchen; Xu, Chongqing; Ma, Junming; Ye, Jie; Mo, Wen
Study Design: Bibliometric analysis. Objective: Cervical spondylotic myelopathy (CSM) has become the most common cause of spinal cord dysfunction. Many topics of CSM still remain controversial. This study aimed to illustrate the overall knowledge structure and development trends of CSM. Methods: Research data sets were acquired from the Web of Science database and the time span was defined as "2000 to 2019." VOS viewer and Citespace software was used to analyze the data and generate visualization knowledge maps. Annual trends of publications, distribution, H-index status, co-authorship status, and research hotspots were analyzed. Results: A total of 2367 publications met the requirement. The largest number of articles was from the United States, followed by Japan, China, Canada, and India. The highest H-index was found for articles from the United States. The highest number of articles was published in Spine . The cooperation between the countries, institutes, and authors were relatively weak. Cervical sagittal alignment, predictive factor, diffusion tensor imaging, and the natural history of CSM may become a frontier in this research field. Conclusion: The number of publications showed an upward trend with a stable rise. Most of the publications are limited to a few countries and institutions with relatively weak interaction. The United States, Canada, Japan, China, and India have made significant contributions to the field of CSM. The United States is the country with the highest productivity, not only in quality but also in quantity. Cervical sagittal alignment, predictive factor, diffusion tensor imaging, and the natural history of CSM are the research hotspots in the recent years.